Literature and postwar Central American poetic criticism in Repertorio Americano (1996-2004) - Montero Corrales, Cristopher (2024)
This article deals with literary criticism in the magazine Repertorio Americano (1996-2004) as a way of understanding the movements of literary criticism and the form of critical thinking and its ideological and literary representations in the Central American region. Specifically, it makes assessments regarding poetic criticism where formal, semantic, and social approaches were privileged, evidencing the formal critical patterns of literary criticism and its representations in the Central American postwar period.